Successful laparoscopic surgery for 14-month-old infant with ovarian torsion - Ahn, Ji Hyun (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology; Korean Urogynecologic Society, 2014)
The prevalence of ovarian torsion is 4.9 among 100,000 females between ages 1 to 20 years. The diagnosis of ovarian torsion in children, especially in infants, is very difficult. Since they cannot explain related symptoms accurately, and reproductive organs lie high in the abdomen, physical examination shows unclear findings. For these reasons, we use imaging studies, such as ultrasonography and magnetic resonance imaging, to diagnose ovarian torsion. However, it is of limited value to diagnose by using these modalities alone. Therefore, clinical suspicion is important for diagnosis. Though pediatric laparoscopic surgery was introduced 20 years ago, it has been widely performed since the mid 1990s with the development of 3-mm instruments. In addition, usually the pediatric operation is done in the pediatric surgery office, even though it is a gynecologic procedure. In addition, laparotomy is still more frequently conducted in current clinical practice, although the frequency of laparoscopic surgery has increased. However, it is thought that expert gynecologic surgeons can perform pediatric laparoscopic operations if they pay attention to some precautions. We report herein the case of a 14-month-old infant who underwent emergency laparoscopic untwisting of ovarian torsion successfully without complications by a gynecologic surgeon, with a brief review of the literature.